Ammonium-tagged ruthenium-based catalysts for olefin metathesis in aqueous media under ultrasound and microwave irradiation - Gułajski, Łukasz; Tracz, Andrzej; Urbaniak, Katarzyna; Czarnocki, Stefan J.; Bieniek, Michał; Olszewski, Tomasz K. (Beilstein Journal of Organic Chemistry, 2019)
The influence of microwave and ultrasonic irradiation on the performance of ammonium-tagged Ru-based catalysts in olefin metathesis transformations in aqueous media was studied. Differences in the catalytic activity in correlation with the nature of the present counter ion and the size of the N-heterocyclic carbene (NHC) ligand were revealed. The presented methodology allows for preparation of a variety of polar and non-polar metathesis products under environmentally friendly conditions.
Keywords: catalysis; green chemistry; microwave; N-heterocyclic carbene; olefin metathesis; ruthenium; ultrasound

Olefin Metathesis: Theory and Practice - Grela, K. (Wiley-VCH, 2014)

Handbook of Metathesis - Grubbs, R. H.; Wenzel, A. G.; O’Leary, D. J.; Khosravi, E. (Wiley-VCH, 2015)

(untitled) - Herbert, M. B.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Fustero, S.; Simón-Fuentes, A.; Barrio, P.; Haufe, G. (Chem. Rev., 2015)

(untitled) - Hoveyda, A. H. (J. Org. Chem., 2014)

(untitled) - Olszewski, T. K.; Bieniek, M.; Skowerski, K.; Grela, K. (Synlett, 2013)

(untitled) - Higman, C. S.; Lummiss, J. A. M.; Fogg, D. E. (Angew. Chem., Int. Ed., 2016)

(untitled) - Hughes, D.; Wheeler, P.; Ene, D. (Org. Process Res. Dev., 2017)

(untitled) - Olszewski, T. K.; Figlus, M.; Bieniek, M. (Chim. Oggi, 2014)

(untitled) - Behr, A.; Vorholt, A. J.; Ostrowski, K. A.; Seidensticker, T. (Green Chem., 2014)

(untitled) - Chikkali, S.; Mecking, S. (Angew. Chem., Int. Ed., 2012)

(untitled) - Leimgruber, S.; Trimmel, G. (Monatsh. Chem., 2015)

(untitled) - Piola, L.; Nahra, F.; Nolan, S. P. (Beilstein J. Org. Chem., 2015)

(untitled) - Guidone, S.; Songis, O.; Nahra, F.; Cazin, C. S. J. (ACS Catal., 2015)

(untitled) - Skowerski, K.; Białecki, J.; Tracz, A.; Olszewski, T. K. (Green Chem., 2014)
And the references cited therein.

(untitled) - Skowerski, K.; Kasprzycki, P.; Bieniek, M.; Olszewski, T. K. (Tetrahedron, 2013)

(untitled) - Lin, Y. A.; Chalker, J. M.; Davis, B. G. (ChemBioChem, 2009)

(untitled) - Lin, Y. A.; Chalker, J. M.; Floyd, N.; Bernardes, G. J. L.; Davis, B. G. (J. Am. Chem. Soc., 2008)

(untitled) - Lin, Y. A.; Chalker, J. M.; Davis, B. G. (J. Am. Chem. Soc., 2010)

(untitled) - Lin, Y. A.; Boutureira, O.; Lercher, L.; Bhushan, B.; Paton, R. S.; Davis, B. G. (J. Am. Chem. Soc., 2013)

(untitled) - Wright, D. B.; Touve, M. A.; Thompson, M. P.; Gianneschi, N. C. (ACS Macro Lett., 2018)

(untitled) - Wang, Z. J.; Jackson, W. R.; Robinson, A. J. (Green Chem., 2015)

(untitled) - Gleeson, E. C.; Wang, Z. J.; Jackson, W. R.; Robinson, A. J. (J. Org. Chem., 2015)

(untitled) - Levin, E.; Ivry, E.; Diesendruck, C. E.; Lemcoff, N. G. (Chem. Rev., 2015)

(untitled) - Szczepaniak, G.; Kosiński, K.; Grela, K. (Green Chem., 2014)

(untitled) - Tomasek, J.; Schatz, J. (Green Chem., 2013)

(untitled) - Diaz Velazquez, H.; Verpoort, F. (Chem. Soc. Rev., 2012)

(untitled) - Burtscher, D.; Grela, K. (Angew. Chem., Int. Ed., 2009)

(untitled) - Connon, S. J.; Blechert, S. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Connon, S. J.; Rivard, M.; Zaja, M.; Blechert, S. (Adv. Synth. Catal., 2003)

(untitled) - Binder, J. B.; Blank, J. J.; Raines, R. T. (Org. Lett., 2007)

(untitled) - Tomasek, J.; Seßler, M.; Gröger, H.; Schatz, J. (Molecules, 2015)

(untitled) - Brendgen, T.; Fahlbusch, T.; Frank, M.; Schühle, D. T.; Seßler, M.; Schatz, J. (Adv. Synth. Catal., 2009)

(untitled) - Matsuo, T.; Yoshida, T.; Fujii, A.; Kawahara, K.; Hirota, S. (Organometallics, 2013)

(untitled) - Lipshutz, B. H.; Aguinaldo, G. T.; Ghorai, S.; Voigtritter, K. (Org. Lett., 2008)

(untitled) - Lynn, D. M.; Kanaoka, S.; Grubbs, R. H. (J. Am. Chem. Soc., 1996)

(untitled) - Claverie, J. P.; Viala, S.; Maurel, V.; Novat, C. (Macromolecules, 2001)

(untitled) - Davis, K. J.; Sinou, D. (J. Mol. Catal. A: Chem., 2002)

(untitled) - Lipshutz, B. H.; Bošković, Z.; Crowe, C. S.; Davis, V. K.; Whittemore, H. C.; Vosburg, D. A.; Wenzel, A. G. (J. Chem. Educ., 2013)

(untitled) - La Sorella, G.; Strukul, G.; Scarso, A. (Green Chem., 2015)

(untitled) - Lipshutz, B. H.; Ghorai, S.; Cortes-Clerget, M. (Chem. – Eur. J., 2018)

(untitled) - Wang, W.; Cui, L.; Sun, P.; Shi, L.; Yue, C.; Li, F. (Chem. Rev., 2018)

(untitled) - Dewaele, A.; Verpoort, F.; Sels, B. (ChemCatChem, 2016)

(untitled) - Mwangi, M. T.; Runge, M. B.; Bowden, N. B. (J. Am. Chem. Soc., 2006)

(untitled) - Hensle, E. M.; Tobis, J.; Tiller, J. C.; Bannwarth, W. (J. Fluorine Chem., 2008)

(untitled) - Kappe, C. O.; Pieber, B.; Dallinger, D. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kappe, C. O. (Angew. Chem., Int. Ed., 2004)

(untitled) - Kappe, C. O.; Dallinger, D. (Nat. Rev. Drug Discovery, 2006)

(untitled) - Chatel, G. (Ultrason. Sonochem., 2018)

(untitled) - Cravotto, G.; Cintas, P. (Chem. Soc. Rev., 2006)

(untitled) - Cravotto, G.; Cintas, P. (Chem. Sci., 2012)

(untitled) - Lupacchini, M.; Mascitti, A.; Giachi, G.; Tonucci, L.; d'Alessandro, N.; Martinez, J.; Colacino, E. (Tetrahedron, 2017)

(untitled) - Banerjee, B. (Ultrason. Sonochem., 2017)

(untitled) - Cravotto, G.; Borretto, E.; Oliverio, M.; Procopio, A.; Penoni, A. (Catal. Commun., 2015)

(untitled) - Cravotto, G.; Gaudino, E. C.; Cintas, P. (Chem. Soc. Rev., 2013)

(untitled) - Varma, R. S. (Green Chem., 2014)

(untitled) - Bruckmann, A.; Krebs, A.; Bolm, C. (Green Chem., 2008)

(untitled) - Dallinger, D.; Irfan, M.; Suljanovic, A.; Kappe, C. O. (J. Org. Chem., 2010)

(untitled) - Garbacia, S.; Desai, B.; Lavastre, O.; Kappe, C. O. (J. Org. Chem., 2003)

(untitled) - Mayo, K. G.; Nearhoof, E. H.; Kiddle, J. J. (Org. Lett., 2002)

(untitled) - Nosse, B.; Schall, A.; Jeong, W. B.; Reiser, O. (Adv. Synth. Catal., 2005)

(untitled) - Debleds, O.; Campagne, J.-M. (J. Am. Chem. Soc., 2008)

(untitled) - Gebauer, J.; Arseniyadis, S.; Cossy, J. (Eur. J. Org. Chem., 2008)

(untitled) - Goldup, S. M.; Pilkington, C. J.; White, A. J. P.; Burton, A.; Barrett, A. G. M. (J. Org. Chem., 2006)

(untitled) - Fürstner, A.; Stelzer, F.; Rumbo, A.; Krause, H. (Chem. – Eur. J., 2002)

(untitled) - Sacco, M.; Charnay, C.; De Angelis, F.; Radoiu, M.; Lamaty, F.; Martinez, J.; Colacino, E. (RSC Adv., 2015)
See for a recent example on simultaneous microwaves-ultrasound irradiation (SMUI) hybrid technology.

(untitled) - Castagnolo, D.; Botta, L.; Botta, M. (J. Org. Chem., 2009)

(untitled) - Gułajski, Ł.; Śledź, P.; Lupa, A.; Grela, K. (Green Chem., 2008)

(untitled) - Knapkiewicz, P.; Skowerski, K.; Jaskólska, D. E.; Barbasiewicz, M.; Olszewski, T. K. (Org. Process Res. Dev., 2012)

(untitled) - Olszewski, T. K.; Jaskólska, D. E. (Heteroat. Chem., 2012)

(untitled) - Tracz, A.; Gawin, A.; Bieniek, M.; Olszewski, T. K.; Skowerski, K. (New J. Chem., 2018)

(untitled) - Skowerski, K.; Szczepaniak, G.; Wierzbicka, C.; Gułajski, Ł.; Bieniek, M.; Grela, K. (Catal. Sci. Technol., 2012)

(untitled) - Skowerski, K.; Wierzbicka, C.; Szczepaniak, G.; Gułajski, Ł.; Bieniek, M.; Grela, K. (Green Chem., 2012)

(untitled) - Skowerski, K.; Białecki, J.; Czarnocki, S. J.; Żukowska, K.; Grela, K. (Beilstein J. Org. Chem., 2016)

(untitled) - Skowerski, K.; Pastva, J.; Czarnocki, S. J.; Janoscova, J. (Org. Process Res. Dev., 2015)

(untitled) - Pastva, J.; Skowerski, K.; Czarnocki, S. J.; Žilková, N.; Čejka, J.; Bastl, Z.; Balcar, H. (ACS Catal., 2014)

(untitled) - Jung, Y.; Marcus, R. A. (J. Am. Chem. Soc., 2007)

(untitled) - Narayan, S.; Muldoon, J.; Finn, M. G.; Fokin, V. V.; Kolb, H. C.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2005)

(untitled) - Pirrung, M. C. (Chem. – Eur. J., 2006)

(untitled) - García-Álvarez, J.; Hevia, E.; Capriati, V. (Chem. – Eur. J., 2018)

(untitled) - Davis, J. G.; Rankin, B. M.; Gierszal, K. P.; Ben-Amotz, D. (Nat. Chem., 2013)

(untitled) - Chanda, A.; Fokin, V. V. (Chem. Rev., 2009)

(untitled) - Butler, R. N.; Coyne, A. G. (Chem. Rev., 2010)